Development of Cerium Oxide-Laden GelMA/PCL Scaffolds for Periodontal Tissue Engineering - Aminmansour, Sahar; Cardoso, Lais M. [UNESP]; Anselmi, Caroline [UNESP]; de Carvalho, Ana Beatriz Gomes [UNESP]; Rahimnejad, Maedeh; Bottino, Marco C. (MDPI, 2024)
This study investigated gelatin methacryloyl (GelMA) and polycaprolactone (PCL) blend scaffolds incorporating cerium oxide (CeO) nanoparticles at concentrations of 0%, 5%, and 10% w/w via electrospinning for periodontal tissue engineering. The impact of photocrosslinking on these scaffolds was evaluated by comparing crosslinked (C) and non-crosslinked (NC) versions. Methods included Fourier transform infrared spectroscopy (FTIR) for chemical analysis, scanning electron microscopy (SEM) for fiber morphology/diameters, and assessments of swelling capacity, degradation profile, and biomechanical properties. Biological evaluations with alveolar bone-derived mesenchymal stem cells (aBMSCs) and human gingival fibroblasts (HGFs) encompassed tests for cell viability, mineralized nodule deposition (MND), and collagen production (CP). Statistical analysis was performed using Kruskal–Wallis or ANOVA/post-hoc tests (α = 5%). Results indicate that C scaffolds had larger fiber diameters (~250 nm) compared with NC scaffolds (~150 nm). NC scaffolds exhibited higher swelling capacities than C scaffolds, while both types demonstrated significant mass loss (~50%) after 60 days (p < 0.05). C scaffolds containing CeO showed increased Young’s modulus and tensile strength than NC scaffolds. Cells cultured on C scaffolds with 10% CeO exhibited significantly higher metabolic activity (>400%, p < 0.05) after 7 days among all groups. Furthermore, CeO-containing scaffolds promoted enhanced MND by aBMSCs (>120%, p < 0.05) and increased CP in 5% CeO scaffolds for both variants (>180%, p < 0.05). These findings underscore the promising biomechanical properties, biodegradability, cytocompatibility, and enhanced tissue regenerative potential of CeO-loaded GelMA/PCL scaffolds for periodontal applications.
Keywords: cerium oxide; electrospinning; gelatin methacryloyl; periodontium; polycaprolactone